Lessons from the reestablishment of Public Health Laboratory activities in Puerto Rico after Hurricane Maria - Margaret C. Hardy (Nature Portfolio, 2019)
Hurricane Maria hit Puerto Rico in 2017 and resulted in a complete loss of activity of the Public Health Laboratories. Here, the authors discuss the approach taken and tools developed to re-establish activity in these laboratories using a quality management system and the lessons learned in this process.